Experiment and Analysis for Utrasonic Particle Detection of Liquid-vapor Mixture in Narrow Rectangular Channel - Hu Yongpan; Tao Leren; Huang Lihao; Zheng Zhigao; Li Qingpu (Zhileng xuebao)
With deionized water as working fluid, ultrasonic particle detection system is applied to two-phase heat transfer process. The ultrasonic attenuation spectrum method is used to measure flow boiling in vertical narrow rectangular channel. The ultrasonic attenuation spectrum, the bubble size distribution and export rate of gas (dryness) under different mass flux of 2.22 kg/(m2?s)，2.86 kg/(m2?s) and 3.49 kg/(m2?s) in the narrow rectangular are obtained by theoretical model and inversion algorithm, respectively. The experiment results show that when the mass flow rate is constant, with an increase of the heating power, ultrasonic attenuation coefficient will increase under the same ultrasonic frequency, the value of D50 will increase and the distribution of dimensions will broaden. Under the same operating conditions, with an increase of the mass flow rate, the value of D50 will decrease and the distribution of dimensions will heighten and narrow. The degree of dryness measured by ultrasonic testing system is higher than the theoretical value, and the measurement are closed to the theoretical values when the dryness is small. The error increases when the dryness increases and the theoretical model should be adjusted in this case.